Design, Synthesis and Molecular Properties Prediction of Novel Quinazoline Derivatives as Potent Antibacterial Agents - Eswararao, S.V.; Venkataramireddy, V.; Srinivasareddy, M.; Kumar, Pramod (Asian Journal of Chemistry, 2017)
A novel series of compounds were synthesized by C-C bond formation of substituted quinazolinones (1) with substituted boronic acids (2) to get 2,4-disubstituted quinazoline (3a-3n) in good to excellent yields. The structures of the new compounds were confirmed by IR, 1H NMR, 13C NMR and mass spectral data. An antibacterial and antifungal activity screening results showed that compounds 3b, 3e, 3i and 3l possess excellent activity against Gram (+), Gram (-) bacteria (S. aureus, Klebsiella species, P. aeruginosa) compared to standard drugs. 3l, 3g and 3n showed better antifungal activity against A. nigeri and C. albicans organisms. In this investigation, the target compounds 3a-3n were subjected to in silico molecular properties prediction and drug likeness by employing Molinspiration (Molinspiration, 2014) and MolSoft (MolSoft, 2007) property explorer tool kits for predicting their high oral bioavailability.